A educação permanente em saúde na perspectiva de gestores da atenção básica - Carvalho, Enderson Rodrigues de (2020)
Introduction: Permanent Health Education (EPS) aims to provide reflections on professional practice, with the participation of all team members in an environment of exchange and learning (BARBOSA, FERREIRA, BARBOSA, 2012). Objective: The research aimed to learn from team managers, in the scope of Primary Care, how the proposal for permanent health education in their work and management spaces has taken place. Methodology: Qualitative research with data collection using the semi-structured interview technique with 25 BA managers in the city of Rio Claro / SP. Data analysis took place through content analysis (CAMARA, 2013). Results: Thematic axes are: Permanent Education in Health: conceptual dimension and Permanent Education in Health: challenges of operationalizing PHE. Conclusion: The study reveals that, although there is a clear concept about Permanent Education in Health, in practice, actions of this are still mixed with those of continuing education, but regardless of this, they are being practiced with exchanges of professional experiences in daily life and / or meetings of team. There are challenges of inadequate dimensioning of professionals and resistance to changes in daily work, but also the power that it presents as a necessary process in daily practice in the health area. Thus, Permanent Education in Health becomes a movement in a continuous process, with the promotion of changes in the work environment and, consequent actions in the attention to users and the community, which can be considered a management tool in the area of health and improvement in the quality of health care.